Pendampingan Berbasis Media Sosial Pada Penderita Covid 19 dengan Isolasi Mandiri di Kecamatan Margadana Kota Tegal - Umriaty; Seventina Nurul Hidayah; Meyliya Qudriani (JPM: Jurnal Pengabdian Masyarakat, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. The virus is mainly transmitted from symptomatic people to other people who are in close proximity through droplets. Social restrictions are the government's policy choice as an effort to reduce transmission. People with COVID-19 have an obligation to limit their interactions with other people. The option of self-isolation at home is taken for patients with mild symptoms. This activity aims to provide assistance to Covid-19 patients. Assistance is provided through social media, namely Whatsapp. There were three families who were given assistance in this activity. The information provided is the treatment of Covid-19 patients at home and the prevention of transmission to family members. In addition to providing information, activities are also carried out in the form of partnerships with the Sumurpanggang Health Center for reporting patient conditions. To meet nutritional needs, partnerships are made with mobile vegetable traders. Assistance activities are carried out since the patient is confirmed positive for Covid-19 through an antigen examination for up to 14 days. As a result, Covid-19 patients were able to go through a period of self-isolation and no new cases were found in family members. Suggestions for the community are optimizing the right information about the care of Covid-19 patients who are self-isolating at home